HUBUNGAN ANTARA PENGETAHUAN PERAWAT TENTANG KESELAMATAN PASIEN DENGAN PENERAPAN PEMBERIAN OBAT DI RUMAH SAKIT “X” - Eva Roos Kusuma Dewi; Dewi Anggraini (STIKes IMC Bintaro, 2018)
Background : Law number 44 of 2009 on hospital, article 43 paragraph (1) requires that hospitals implement patient safety standards. Patient safety standards according to article 43 paragraph (2) are carried out through incident reporting, analyzing, and establishing problem solving in order to reduce the number of unexpected events. The patient’s safety incident is a (medical error), an (adverse event), and (near miss) (Depkes RI, 2015). Patient safety is the main service standard for ensuring hospital quality, the incidence of errors in drugadministration becomes a problem that can damage the good reputation of the hospital. Objective : To determine the relationship between nurses knowledge of patient’s safety with the application of medicine at “X” hospital. Research method : Respondent of permata pamulang hospital nurse, research type used is quantitative Research using cross sectional research design, 101 sample technique using chi square statistic test. Result of research : Nurse characteristic mostly young adult < 30 years (85,1%), have low education (72,3%), length of work < 2 years (54,5%), nurse with good knowledge (71,3%), a bargain that does not apply the drug properly (55.4%). Conclusion : There is a relationship between nurse knowledge about patient safety with drug application p-value 0,018. Suggested socialization about patient safety.